La poesía de Sedulio y Eugenio de Toledo en dos inscripciones hispanas del siglo VII* - Gilsanz Stanger, Francisco (Cuadernos de Filología Clásica. Estudios Latinos, 2006)
In this article I propose a new edition for two inscriptions from Hispania, both of them sharing their date in the seventh century, their nature of carmina epigraphica and to be an adaptation of two christian poet’s verses, Sedulio and Eugenio from Toledo respectively. The first one, coming from Alburquerque (Badajoz), is preserved incomplete, but its initial lines (1-4) could be completed if it is considered that they copy with small differences some verses from the Carmen Paschale composed by Sedulio (3.92-94 and 206). In the second part, I regard as one inscription (coming from Gerena, Sevilla) two fragments thougtht before to be two separate epigraphs: the new edition of the whole allows to date the poem in 662 AD and to have a better knowledge of its imitation of Eugenio from Toledo (Carm. 25.1-3, 18 y 21). Besides the new edition of both inscriptions there is a study of their contents and formal features, from the point of view of the literary adaptation in them.